2013
DOI: 10.1371/journal.pone.0069805
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genes May Pass from Food to Human Blood

Abstract: Our bloodstream is considered to be an environment well separated from the outside world and the digestive tract. According to the standard paradigm large macromolecules consumed with food cannot pass directly to the circulatory system. During digestion proteins and DNA are thought to be degraded into small constituents, amino acids and nucleic acids, respectively, and then absorbed by a complex active process and distributed to various parts of the body through the circulation system. Here, based on the analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 36 publications
0
53
0
1
Order By: Relevance
“…During digestion this DNA may pass through the gut wall (barrier) un- or only partly digested, thus appearing in the circulation (or perhaps other tissues) from where bat ticks can take it up with their blood meal. In support of this possibility, it has recently been verified that meal-derived DNA fragments (even long ones) can avoid degradation and through not-yet-known mechanisms enter the circulation, at least in humans [52]. …”
Section: Discussionmentioning
confidence: 99%
“…During digestion this DNA may pass through the gut wall (barrier) un- or only partly digested, thus appearing in the circulation (or perhaps other tissues) from where bat ticks can take it up with their blood meal. In support of this possibility, it has recently been verified that meal-derived DNA fragments (even long ones) can avoid degradation and through not-yet-known mechanisms enter the circulation, at least in humans [52]. …”
Section: Discussionmentioning
confidence: 99%
“…It is not only human cells that shed their nucleic acids into the blood: DNA from plant-based foods has been detected (15), and other life forms such as viruses, bacteria, and fungi release their DNA and RNA into the blood, a phenomenon which has been exploited to determine the presence of infectious disease (12,16) and to measure alterations of the virome due to pharmacological immunosuppression (17). There are roughly an order of magnitude more nonhuman cells than nucleated human cells in the body (18,19); combining this observation with the average genome sizes of a human, bacterium, and virus (Gb, Mb, and kb, respectively) suggests that approximately 1% of DNA by mass in a human is derived from nonhost origins.…”
mentioning
confidence: 99%
“…Animal and human feeding studies have demonstrated that fragmented dietary DNA may resist the digestive process (Rizzi et al, 2012) and even complete genes can transgress the gut barrier (Spisák et al, 2013). Taking into account this scenario, the present findings might imply that bats have access to free-living bodonids and at least the DNA of bodonids might pass through the oropharyngeal or gastrointestinal mucosa of bats into their circulation.…”
mentioning
confidence: 67%